Escape Room para niños con TDAH en la asignatura de Matemáticas del segundo año de Educación General Básica - Guevara Llerena, Karen Lizeth (2023)
The use of digital resources for children with deficit attention and hyperactivity disorder is very scarce since the Ministry of Education's curriculum does not provide particular care for children with this disorder. In this sense, the objective of this research work was to create an Escape Room as a didactic strategy for the second-year EGB mathematics subject aimed at children with ADHD, it is essential to know that an Escape Room is a game that takes place in a natural environment, and the objective is to solve puzzles using clues and escape from the room by receiving some reward. The themes from the student's book were used to develop the resource, where the challenges framed in the learning line of the subject were created. Applied research with a non-experimental design and an exploratory scope was used, in which no situation was generated. However, already existing phenomena were observed to find solutions to real problems. Finally, it is concluded that incorporating an educational Escape Room can be an alternative to capture the attention and motivation of students with ADHD.